Leveraging design thinking to tackle contemporary admissions challenges in health professions education - Adina O. Davidson; Wendy C. Cox; Heather Azzu; Kelly Womack-Adams; Jacqueline E. McLaughlin (PLoS ONE, 2026)
Purpose This study illustrates the use of design thinking (DT) as a structured, participatory approach to explore contemporary complex challenges in health professions admissions, including the rise of generative AI, remote interviews, and the elimination of standardized admissions tests. This work focuses on stakeholder-driven problem framing and idea generation rather than evaluating outcomes. Methods A two-hour workshop engaged 15 purposively sampled stakeholders, including faculty, staff, application readers, and student ambassadors, in collaborative problem framing, ideation, and rapid prototyping of admissions concepts. Generative artifacts (brainstorming outputs, reflection worksheets, facilitator notes) and post-session surveys were analyzed using thematic synthesis and descriptive statistics to characterize emergent ideas and participant perspectives. Major findings Participants generated ideas that clustered into three major themes: interview restructuring, GenAI integration and compliance, and broadening of admissions criteria, illustrating how stakeholders reframed challenges and proposed diverse solution pathways. Survey responses reflected descriptive indicators of participant experience, suggesting the workshop supported creative problem solving (Mean 4.7 ± 0.5), idea generation (4.8 ± 0.4), and collaboration (4.4 ± 0.5). Conclusions Findings suggest that DT offers a structured, iterative framework for stakeholder-driven idea generation and problem reframing in an evolving admissions context. The workshop demonstrates the potential of collaborative, reflective processes to surface assumptions and generate diverse perspectives to inform future exploration of admissions practices.